The Challenges of Chinese University Leaders During the COVID-19 Pandemic Period: A Case Study Approach - Zhang, Xiudi; Tian, Xiaoming (Frontiers in Psychology, 2022)
The outbreak of COVID-19 had a profound impact on the practice of university leadership in China. Five leaders were interviewed about their challenges at Z University. The challenges they faced manifested in the government’s closed management requirements and the students’ demands for freedom of entry and exit, the dynamic and flexible disciplinary development and the rigid teaching evaluation, and big data-enabled governance and the habit of human experience-oriented management. In response to these challenges, this study proposes suggestions for Z university leaders in the post-pandemic era: establishing rules and regulations with a relaxed degree, tolerating ambiguity in online teaching, improving the ability of intelligent technology, and taking opportunities to learn.